2016
DOI: 10.1063/1.4942637
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature weak ferromagnetism in Sn1−xMnxSe2 2D films grown by molecular beam epitaxy

Abstract: We discuss growth and magnetic properties of high-quality two dimensional (2D) Sn1−xMnxSe2 films. Thin films of this 2D ternary alloy with a wide range of Mn concentrations were successfully grown by molecular beam epitaxy. Mn concentrations up to x ≈ 0.60 were achieved without destroying the crystal structure of the parent SnSe2 2D system. Most important, the specimens show clear weak ferromagnetic behavior above room temperature, which should be of interest for 2D spintronic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 21 publications
1
28
2
Order By: Relevance
“…Many previous studies have tried various ways to induce ferromagnetic ordering into non-magnetic 2D van der Waals materials. This includes various types of defect engineering [72,73,74,75,76,77,78,79], induced magnetism via strain [80], compositional alloying [71], or the proximity effect [16,17,81] to induce a magnetic moment at the interface of the non-magnetic 2D material.…”
Section: Magnetism In Van Der Waals Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies have tried various ways to induce ferromagnetic ordering into non-magnetic 2D van der Waals materials. This includes various types of defect engineering [72,73,74,75,76,77,78,79], induced magnetism via strain [80], compositional alloying [71], or the proximity effect [16,17,81] to induce a magnetic moment at the interface of the non-magnetic 2D material.…”
Section: Magnetism In Van Der Waals Materialsmentioning
confidence: 99%
“…A few years later, scientists began studying the effects of depositing magnetic impurities into non-magnetic 2D semiconductors during MBE growth [71,82,83]. There has been many theoretical predictions about magnetic doping of Mn, Cr, and V into TMDCs such as MoS 2 [84], which is a motivating factor for attempting these studies.…”
Section: Magnetism In Van Der Waals Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular beam epitaxy (MBE) was also demonstrated to prepare high‐quality epitaxial films on graphene‐terminated 6H‐SiC(0001) substrate . MBE also allowed for the fine control of non‐stoichiometric phase preparation . There are many other methods to synthesise layered TMDs, for example ultrasonication in solvents, physical vapor deposition, hydrothermal synthesis, and more recently, Tedstone et al described a number of methods to synthesise TMD materials with transition‐metal dopants.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 99%
“…Intercalating Mn into MoS 2 monolayers has been reported with doping levels of ∼2 at% Mn, however this caused a loss of two‐dimensionality due to competing MnS 3‐dimensional structures. Nevertheless, weak ferromagnetism in Sn 1‐ x Mn x Se 2 , even at room temperature has been reported . Cheng et al demonstrated that several transition metals can be incorporated to WS 2 nanoflakes, and while their doping with Gd 3+ was employed for magnetic resonance imaging, one could easily envision translating such materials into spintronic applications.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 99%